A Review of Chinese Species of the Genus Oides Weber, 1801 (Coleoptera: Chrysomelidae: Galerucinae) - Meixia Yang; Jian Shen; Changping Ding; Xingke Yang (Insects, 2024)
In this study, 25 species of Oides Weber from China were reviewed. Among them, the following seven new species are described: Oides angustasp. nov., O. cystoprocessasp. nov., O. paraborerisp. nov., O. parabowringiisp. nov., O. parathibettanasp. nov., O. shimenensissp. nov., and O. yunnanensissp. nov.; Oides innocua Gahan has been recorded in China for the first time. A key to all the Chinese Oides species is provided.